Unmasking Sensory Defects of Olive Oils Flavored with Basil and Oregano Using an Electronic Tongue‐Chemometric Tool. (25th June 2019) - Bobiano, Marta; Rodrigues, Nuno; Madureira, Marta; Dias, Luís G.; Veloso, Ana C. A.; Pereira, José A.; Peres, António M.
Abstract: Olive oil price and consumers' preference depend on the commercial grade classification that can decrease if any sensory defect is perceived leading to an economic loss. Enriched oils, obtained by incorporating dried aromatic herbs, spices, or essential oils, which is a common practice in the Mediterranean region, are commercially available. This practice may conceal the fraudulent purpose of masking the perception of sensory defects. The detection of this type of fraud is a difficult task, requiring sensory analysis. Thus, in this study, extra‐virgin and lampante olive oils, the latter classification being due to the perception of an intense winey‐vinegary defect, were deliberately enriched with different amounts of basil‐dried herbs and oregano‐dried herbs. Sensory analysis showed that, depending on the aromatic herb and on the added amount (0.011–0.110 g herb per kg oil), the defect intensity could be masked leading to an erroneous classification of flavored lampante oils as flavored virgin oils. In contrast, the electronic tongue‐chemometric approach could unmask the defect in flavored oils (predictive sensitivities: 70–78%) and semiquantitatively discriminate flavored oils according to the added levels of basil or oregano (predictive sensitivities: 93–100%). The electronic tongue approach showed satisfactory unmasking performance when compared with the sensory panel, and so, its future application as a quality control taste‐sensor device for disclosing olive oil sensory defects masked by the incorporation of flavoring agents may be forseen.